Two distinct classes of Ran-binding sites on the nucleoporin Nup-358 - Yaseen, Nabeel R. (The National Academy of Sciences, 1999)
Nup-358 is a giant nucleoporin located at the tips of the cytoplasmic fibrils of the nuclear pore complex (NPC). Its contains four RBH (RanBP1-homologous) domains and a zinc finger domain with eight zinc finger motifs. Using three recombinant fragments of Nup-358 that comprise two of the RBH domains and the zinc finger domain, we show that both RanGDP and RanGTP bind to Nup-358 in vitro. The RBH domains bound either RanGDP or RanGTP. Interestingly, the zinc finger domain was found to bind RanGDP exclusively. Zinc chelation by EDTA treatment abolished the binding of RanGDP to the zinc finger domain without affecting the binding of Ran to the RBH domain. Ultrastructural studies with RanGDP-conjugated colloidal gold in digitonin-permeabilized cells showed a large number of Ran-binding sites on the cytoplasmic fibrils of the NPC. Of those, only a portion that is closer to the central axis of the NPC was sensitive to RanBP1 competition, suggesting that most of the RBH domains of Nup-358 are situated closer to the central axis of the NPC than the zinc finger domain. Thus, the RBH and the zinc finger domains of Nup-358 were identified as two different classes of Ran-binding sites with distinct, ultrastructural locations at the NPC.